2019
DOI: 10.9734/jeai/2019/v36i230230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Treatments and Containers on Chilli Seed Viability

Abstract: An experiment was conducted to investigate the influence of fungicides and packaging materials on longevity of chilli seed (variety: RCH-1). The seeds were treated with 15 fungicides and were kept in three containers viz. Metal box, Cloth bag and Plastic zipling bag up to 12 months under ambient conditions in seed pathology laboratory of Department of Seed Science & Technology, CCSHAU, Hisar, India. The samples were drawn at quaterly intervals for ascertaining the seed quality parameters. The seeds treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It also reported that the proper storage condition and storage containers can maintain seed health status as well as seed viability and vigour in okra [5]. Therefore the study entitled the "Effect of seed treatments and containers on chilli and brinjal seed viability" was carried out [6].…”
Section: Introductionmentioning
confidence: 99%
“…It also reported that the proper storage condition and storage containers can maintain seed health status as well as seed viability and vigour in okra [5]. Therefore the study entitled the "Effect of seed treatments and containers on chilli and brinjal seed viability" was carried out [6].…”
Section: Introductionmentioning
confidence: 99%